Empagliflozin reduces myocardial ketone utilization while preserving glucose utilization in diabetic hypertensive heart disease: A hyperpolarized 13C magnetic resonance spectroscopy study. Issue 2 (18th October 2018) - Abdurrachim, Desiree; Teo, Xing Qi; Woo, Chern Chiuh; Chan, Wei Xin; Lalic, Janise; Lam, Carolyn S. P.; Lee, Philip Teck Hock
Abstract : Aim: To investigate the effects of the sodium‐glucose co‐transporter‐2 inhibitor empagliflozin on myocardial ketone body utilization in diabetic, obese rats with spontaneously hypertensive heart failure (SHHF), after 6 months of treatment. Materials and Methods: Myocardial ketone body utilization was measured in vivo real time using a novel ketone probe (hyperpolarized [3‐ 13 C]acetoacetate) and magnetic resonance spectroscopy (MRS). Myocardial glucose utilization and cardiac function were also determined in vivo using hyperpolarized [1‐ 13 C]pyruvate MRS and magnetic resonance imaging (MRI), respectively. Myocardial fatty acid uptake and liver ketogenesis were assessed via protein expression. Results: At baseline, myocardial ketone and glucose utilization were both higher in SHHF compared with control rats. Six months of empagliflozin treatment in SHHF rats was associated with less obesity, lower blood pressure, reduced blood glucose and insulin levels, and increased fasting blood β‐hydroxybutyrate levels, as expected. Contrary to the hypothesis, myocardial ketone body utilization was lower in empagliflozin‐treated SHHF rats, while glucose utilization and cardiac function were unaltered and hepatic congestion was reduced, compared with vehicle‐treated SHHF rats. Conclusions: In diabetic hypertensive heart disease, empagliflozin reduces afterload without altering myocardial function and glucose utilization in the face of falling blood glucose levels, but does not enhance myocardial ketone utilization despite increased circulating levels.